EVALUASI SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) PADA PENYUSUNAN LAPORAN KEUANGAN DI DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN SLEMAN - Desti Amalia; Abdul Halim (Behavioral Accounting Journal, 2021)
This study evaluates the effectiveness of the implementation of SPIP in the Finance Sub-Section on the process of preparing financial reporting for the Sleman Industry and Trade Office (Disperindag) by referring to Government Regulation Number 60 of 2008 and Regulation of the Head of BPKP Number 4 of 2016. level 4 “Managed & Scalable”. This figure shows that the Government's Internal Control System (SPIP) in the process of preparing SKPD financial reports at the Disperindag Sleman has been effective but not yet optimum. Internal control practices in the process of preparing financial statements have been implemented in accordance with applicable policies, are automated through the Regional Financial Information System, and are documented. However, there are several weaknesses, namely the absence of an evaluation on the development of Human Resources and restrictions on access to financial information systems, as well as evaluation activities that do not use the information system to monitor the progress of follow-up evaluations automatically.